Research in personnel and human resources management. volume 40 - Buckley, M. Ronald; Wheeler, Anthony R.; Baur, John E. (Assistant professor); Halbesleben, Jonathon R. B. (Research in personnel and human resources management, 2022)
Volume 40 of Research in Personnel and Human Resources Management offers several original scholarly contributions written by thought leaders in the field of human resources management. These chapters feature the latest research exploring emerging new areas of HRM management. Chapters include analysis of "other-rating" alternatives to traditional self-survey information gathering, how governance mechanisms might be utilized to help firms achieve a balance between alignment and disruption, multi-stakeholder approaches to constructive deviance in the workplace, and how thoughtfully constructed incentives can be used to improve other outcomes such as safety, quality, prosocial behaviors, and creativity.